Effects of the etonogestrel contraceptive implant (Implanon®) on bone metabolism during lactation: a prospective study. Issue 2 (1st December 2016) - Iltemir Duvan, Candan; Onaran, Yuksel; Aktepe Keskin, Esra; Yüce, Ebru; Yanık, Burcu; Kafali, Hasan; Ozturk Turhan, Nilgun
Abstract : Aim: To evaluate the effects of the etonogestrel contraceptive implant (Implanon ® ) on bone metabolism in lactating women using markers for bone formation and resorption. Study design: This single-centre, prospective cohort study was conducted in Turgut Ozal University Medical Faculty Obstetrics and Gynecology Department with healthy lactating women aged between 24 and 38 years to compare the effect on bone metabolism of 6 months' use of either the implant or a non-hormonal contraceptive method. The study group ( n =25) used an implant and the control group ( n =25) used a non-hormonal contraceptive intrauterine device inserted 40 days' postpartum. Bone metabolism differences at the time of insertion and after 6 months were assessed quantitatively by biochemical analysis of serum and urine samples. Results: At baseline, serum levels of bone metabolism parameters were similar for the two groups. In the implant group, serum alkaline phosphatase (ALP) levels decreased ( p =0.004) and total protein levels increased ( p =0.045) at 6 months. In the control group, serum levels of bone metabolism parameters did not change at 6 months compared to baseline. However, serum levels of phosphorus ( p =0.013) and ALP ( p =0.003) decreased at 6 months compared to baseline. Conclusion: Six months' postpartum use of Implanon was found to have no deleterious impact on bone turnover in healthy lactating women.